Towards Adaptive Evolutionary Architecture - Bak, Sebastian Hølt; Rask, Nina; Risi, Sebastian (Evolutionary and Biologically Inspired Music, Sound, Art and Design, 2016)
This paper presents first results from an interdisciplinary project, in which the fields of architecture, philosophy and artificial life are combined to explore possible futures of architecture. Through an interactive evolutionary installation, called EvoCurtain, we investigate aspects of how living in the future could occur, if built spaces could evolve and adapt alongside inhabitants. As such, present study explores the interdisciplinary possibilities in utilizing computational power to co-create with users and generate designs based on human input. We argue that this could lead to the development of designs tailored to the individual preferences of inhabitants, changing the roles of architects and designers entirely. Architecture-as-it-could-be is a philosophical approach conducted through artistic methods to anticipate the technological futures of human-centered development within architect.